Persepsi Pemenang Terhadap Penyelanggaraan Pemilihan Pelajar Pelopor di Indonesia - Widjajanti, Endang (Jurnal Keselamatan Transportasi Jalan (Indonesian Journal of Road Safety), 2022)
This study aims to know the perception of the winner about implementation of the Pioneer Student selection for Traffic and Road Transport Safety at the district / city, provincial and national levels. Data collection was carried out through online interviews with google forms to the finalists of the national-level pioneer students who were also winners at the provincial and district/city levels. The analysis used in this study is a descriptive analysis method. A very attractive impression of implementation at the national level relatively higher than the implementation at the provincial level and at the district / city level. There was still less interesting material and / or speakers and time constraints caused the delivery of the material to be less than optimal. The benefits that the finalists get from the selection of pioneer students at all levels of organizing are increased insight into traffic safety and road transport and the improvement of traffic behavior. There were still few scientific works from the pioneer student winners that were followed up and their function as a Traffic and Road Transport safety ambassador for high school students has not been properly accommodated.